Institutional response to criminalization decisions - Wilenmann, Javier (International journal of law, crime and justice, 2017)
Criminalization decisions are often connected with political conflict. When linked to a legislative decision, criminalization emanates from a relevant political input: a politically significant group seeks to criminalize a conduct out of interest-, value- or knowledge-commitment. The institutional system has to work that input in such a way that conflict can be absorbed. The article provides a typology for the analysis of the strain that criminalization demands and criminalization decisions imply for the institutional system and the way in which the legislature and control organs such as constitutional courts can react to it. By focusing in the US and German systems, the article then attempts to reconstruct the effects that different reactions have on the institutional system. By proceeding this way, the article aims at showing the shortcomings of the traditional, justice-centered critical analysis of criminalization and the performance that an alternative approach, centered on institutional and political analysis, can have.